Anti-NMDAR1 antibody impairs dendritic branching in immature cultured neurons - Jorratt, Pascal; Petruskova, Aneta (Journal of applied biomedicine, 2024)
Anti-N-methyl D-aspartate receptor (anti-NMDAR) encephalitis is an autoimmune disorder characterized by IgG antibodies targeting NMDAR. The prevalence is remarkably higher in women and some develop the condition during pregnancy. While immunotherapies have shown good outcomes for pregnant mothers and their infants, the impact on early neurodevelopment remains elusive. This study investigates the effects of anti-NMDAR antibody on the development of primary cortical cultures. Anti-NMDAR antibody was administered to the cultures at day in vitro 5 for the following 5 days to assess dendritic branching and arbor complexity, and at day in vitro 14 for measuring the expression of brain-derived neurotrophic factor (BDNF) and synaptic proteins. Immature cultured neurons treated with anti-NMDAR antibody exhibited impaired dendritic branching and arbor complexity. Interestingly, BDNF expression was unaffected in mature neurons. Additionally, GluN1 expression, a mandatory NMDAR subunit, was significantly reduced, while no significant alterations were observed in PSD-95, gephyrin and synaptophysin expression. These findings shed light on the structural and synaptic impacts of anti-NMDAR antibody on immature neurons, providing evidence for their consequences in early neuronal development.
Keywords: Neurons; synaptofysin; Nerve Tissue Proteins; Synaptophysin; zvířata; Female; protein PSD-95; Anti-NMDAR encephalitis; Neuronal development; Receptors, N-Methyl-D-Aspartate; neurony; Carrier Proteins; BDNF; Brain-Derived Neurotrophic Factor; Dendritic branching; proteiny nervové tkáně; Dendrites; dendrity; Animals; Disks Large Homolog 4 Protein; krysa rodu Rattus; Rats; receptory N-methyl-D-aspartátu; kultivované buňky; ženské pohlaví; mozkový neurotrofický faktor; membránové proteiny; Synaptic proteins; Membrane Proteins; Cells, Cultured; transportní proteiny